Development of a low-cost air sensor package and indoor air quality monitoring in a California middle school: Detection of a distant wildfire. (2nd September 2019) - Kaduwela, Ajith P.; Kaduwela, Amal P.; Jrade, Ely; Brusseau, Matthew; Morris, Sean; Morris, Jennifer; Risk, Valerie
ABSTRACT: A low-cost air sensor package was used to monitor indoor air quality (IAQ) in a classroom at the Albany Middle School in the San Francisco Bay Area of California. A rapid increase in carbon dioxide (CO2 ) was observed in the classroom as soon as it is occupied. When the classroom is unoccupied, the CO2 levels decay slowly toward the outdoor background level. All high CO2 concentrations observed inside the classroom, above the outdoor background, was due to exhaling of the occupants. The CO2 concentrations generally exceed the recommended level of 1000 ppb towards the end of the school day. The exceedances and slow decay may suggest that the ventilation rate in this school is not sufficient. The particulate level in the classroom was low until a distant wildfire advected large amount of particulate matter to the San Francisco Bay Area. Very high (10–15 times compared to the background) particle numbers (per m 3 of particles with diameter >0.3 µm) were observed in the classroom during the wildfire. These particles were relatively small (0.3–1.0 µm) and the filters (MERV 8) of the ventilation system were unable to filter them out. Therefore, the measurements made by low-cost particle counters can inform the school administrators of adverse IAQ during future wildfire (or other combustion) events. The particle number was independent of the occupation before and during the wildfire suggesting that all observed particles were infiltrated into the classroom from outside. Consistent with previous studies, no appreciable increase in the local ambient CO2 background was observed during this distant wildfire event. Implications : Low-cost air sensors are effective in monitoring indoor air quality in classrooms. The CO2 levels in classrooms are mainly generated indoors due to exhalation of occupants. Concentration of CO2 generally exceed the recommended level of 1000 ppb towards the end of the school day. In contrast, the particulate matter mostly comes from outdoors and small particles penetrate though the filters normally used at schools. Distant wildfires do not increase the local CO2 background appreciably, but significantly increase the particulate matter concentrations both indoors and outdoors. Further investigations are needed to assure that ventilation rates in classrooms are sufficiently health protective.